PENGARUH MODAL, TENAGA KERJA, DAN BAHAN BAKU TERHADAP PENDAPATAN INDUSTRI MEBEL KAYU DI KOTA BANJARMASIN (Studi Kasus Kelurahan Alalak Tengah Kecamatan Banjarmasin Utara) - MUHAMMAD JAHRANI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This study almed to (1) analyzentheneffect of capital, labor, andnraw material tobthe income of wooden furniture industry; (2) to find out which factors dominantly infact the income of wooden furniture industry.The scope of this study took the case study area in Kelurahan Alalak Tengah, Kecamatan Banjarmasin Utara, Kota Banjarmasin. Thendata sources are primaryndatanobtained through interviews and questionnaires to be processed by using multiple regression analysis which will be tested through fbtest (simultaneously) and t test (partially).The resultsnofmthisbstudynindicate that the capital, labor, and raw materials individually (partially) and simultaneously have a positive and significant effect on the income of wood furniture industry. The most dominant factor affecting the income of wooden furniture industry is raw material.Keywords : Capital, Labor, Raw Material, Income of Wood Furniture Industry.